The commercialization of news in the nineteenth century - Baldasty, Gerald J. (Book collections on Project MUSE., 1992)
This work traces the major transformation of newspapers from a politically based press to a commercially based press in the 19th century. Gerald J. Baldasty argues that broad changes in American society, the national economy and the newspaper industry brought about this dramatic shift.